SOSIALISASI KEGIATAN PLP II - Indah Permata Sari Lase; Lies Dian Marsa Ndraha (Haga : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this service is to inform the goals and benefits of carrying out the second school experience practicum activities to all PLP II participating students in supporting lecture activities. The method of implementing this service is carried out in the form of outreach to participants about how they will prepare when they will face various obstacles and challenges in the school field practice. The results of this dedication make students able to prepare themselves and be responsive to the conditions that occur in the field where they practice.